Effect of Polarization Fatigue on Harvesting Energy Using Pyroelectric Materials - Saber Mohammadi (Advances in Materials Science and Engineering)
The phenomenon of polarization fatigue in ferroelectric materials is defined and the effect of this phenomenon on harvested energy using these materials has been studied. In order to illustrate this effect, the harvested energy using PZN-4.5PT single crystal was compared in two cases of fatigued and nonfatigued samples. The results have been calculated between two temperatures of 100 and 130°C using Ericsson thermodynamic cycle.